Recombinant xylanase production by Escherichia coli using a non-induced expression system with different nutrient sources - Mendonca, Elenira H. M.; Avanci, Nilton Cesar; Romano, Luis Henrique; Branco, Daniel Lopes; Padua, Alessandra Xavier de; Ward, Richard John; Baptista Neto, Alvaro de [UNESP]; Lourenzoni, Marcos Roberto (Springer, 2020)
The application of enzymes for sustainable and low-environmental impact industrial processes requires high-level enzyme production at low-cost. A promising strategy is the use of a high efficiency heterologous protein expression system using E. coli and the pT7BsXA vector encoding the GH11 xylanase from Bacillus subtilis with promoter, replication origin and signal peptide sequences from B. subtilis (Ruller et al. 2006). This expression system produces high amounts of enzyme that are secreted to the culture broth. The present study aimed to maximize the xylanase production by this system through evaluation of culture medium composition. Different culture media previously described in the literature together with compositions derived from agro-industrial residues were evaluated. A culture medium derived from agro-industrial residues using sugarcane molasses as carbon source showed a 9-fold increase in enzyme production (195,000 U/L) in relation to LB medium and the lowest production cost, which was 8.5-fold lower than LB medium using sugarcane molasses as carbon source and brewer's yeast as vitamin source in shaker experiments. In a bioreactor experiment the best production medium promoted an 8.5-fold higher production at a 10.8-fold lower cost as compared to shaker LB cultivation.
Keywords: Xylanase; Recombinant enzymes; Bioprocess; Agro-industrial residues; E; coli